A imagem do pensamento e o ensino de filosofia - Valério, Luís Carlos Boa Nova (2010)
The following paper aims to ponder on the problems of Philosophy teaching from the concept of thought image formulated by Gilles Deleuze, being image the orientation the thought gives itself. Such orientation comes from subjective presuppositions (common sense in general or pré-philosophy) and objectives (scientific sense), responsible for the concepts given in Philosophy in the strict form of propositions. We intended to go through how much of the problems in teaching high-school philosophy are due to the learning of the philosophical thought restricted to representation, it means, when presuppositions decide on the meaning and sense in the relation of the concept with the object. Such thought is given by the orientation of an image that naturally inclines it to truth and safe by the good will of the thinker who prejudges all, deciding on the true and false through the square of the representation: concept identity, analogy of judgments, the opposition of the predicate, and the similitude of the perception. The image of the thought, meaning the dogmatic image of the thought, imposes to the teaching of Philosophy and, especially, to the learning of thinking, a hindrance to a beginning without presuppositions in Philosophy, to a thought on the difference capable of establishing concepts to new ways of feeling, thinking, seeing, listening, speaking, and acting.